Influences from working memory, word and sentence reading on passage comprehension and teacher ratings. (8th July 2021) - Kirschmann, Nicole; Lenhard, Wolfgang; Suggate, Sebastian
Abstract : Reading fluency is a major determinant of reading comprehension but depends on moderating factors such as auditory working memory (AWM), word recognition and sentence reading skills. We investigated how word and sentence reading skills relate to reading comprehension differentially across the first 6 years of schooling and tested which reading variable best predicted teacher judgements. We conducted our research in a rather transparent language, namely, German, drawing on two different data sets. The first was derived from the normative sample of a reading comprehension test (ELFE‐II), including 2056 first to sixth graders with readings tests at the word, sentence and text level. The second sample included 114 students from second to fourth grade. The latter completed a series of tests that measured word and sentence reading fluency, pseudoword reading, AWM, reading comprehension, self‐concept and teacher ratings. We analysed the data via hierarchical regression analyses to predict reading comprehension and teacher judgements. The impact of reading fluency was strongest in second and third grade, afterwards superseded by sentence comprehension. AWM significantly contributed to reading comprehension independently of reading fluency, whereas basic decoding skills disappeared after considering fluency. Students' AWM and reading comprehension predicted teacher judgements on reading fluency. Reading comprehension judgements depended both on the students' self‐concept and reading comprehension. Our results underline that the role of word reading accuracy for reading comprehension quickly diminishes during elementary school and that teachers base their assessments mainly on the current reading comprehension skill. Highlights: What is already known about this topic Reading fluency, auditory working memory and basic word recognition skills are predictors of reading comprehension. The orthographic depth of a language influences the acquisition of reading skills. Teacher judgements correspond moderately with actual students' performances. What this paper adds In German, sentence reading fluency is a better predictor of reading comprehension than word reading fluency, from the first grades onwards. Basic word recognition skills did not predict reading comprehension in German from the second grade onwards. Self‐concept, working memory and reading comprehension predict teacher judgements concerning reading fluency and comprehension. Implications for theory, policy or practice The association between accurate word decoding and comprehension decreases across the first grade in transparent orthographies. Fluency at the word and sentence level best predicts reading comprehension and should be preferred over accuracy measures, at least in German.